Porous high-entropy perovskite composite material and preparation method and application thereof
By doping Mn2+, Co2+, Ni2+ and Cu2+ in LaFeO3 oxide, a porous high-entropy perovskite composite material of La(Mn0.2Fe0.2Co0.2Ni0.2Cu0.2)O3 was prepared, which solved the problem of poor specific surface area and specific capacitance value of LaFeO3 material, and significantly improved the electrochemical performance of the electrode material.
Patent Information
- Application Number
- CN202411737778.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
The specific surface area and specific capacitance value of the existing LaFeO3 oxide materials affect their performance as a supercapacitor electrode material.
By doping the substituted part of Fe3+ with Mn2+, Co2+, Ni2+ and Cu2+ on the basis of the oxide LaFeO3, a porous high-entropy perovskite composite material with the chemical formula La(Mn0.2Fe0.2Co0.2Ni0.2Cu0.2)O3 was prepared, and a metal organic frame gel was used as a template for the sintering process.
The specific surface area and porous structure of high-entropy perovskite composites are increased, more electrochemically active sites are exposed, and more abundant electrolyte ion transport channels are provided, thereby improving the electrochemical performance of the electrode materials.
Smart Images

Figure CN119626789A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a porous high-entropy perovskite composite material and a preparation method and application thereof. Background Art
[0002] As the energy crisis becomes increasingly serious, electrochemical energy storage technology has been widely developed. As one of the important energy storage devices, supercapacitors have attracted much attention due to their high power density, fast charge and discharge speed, and long cycle life. Generally speaking, the performance of supercapacitors essentially depends on the electrode materials. Therefore, the development of new energy storage materials with excellent electrochemical properties is of great significance to improving the performance of supercapacitors.
[0003] In recent years, high entropy oxides have been considered as one of the potential candidates for new functional materials. High entropy oxides are usually composed of five or more metal oxides to form a single-phase solid solution with random occupancy. Due to the high entropy effect, the premix of multi-component oxides mainly transforms into a single-phase crystal structure such as perovskite, spinel or rock salt, rather than forming a multi-component intermetallic phase. Thanks to the ideal maximum doping model, high entropy oxides have better structural stability, better mechanical properties and excellent electrochemical activity than single metal oxides and multiple intermetallic oxides. Therefore, compared with traditional low entropy oxide materials, high entropy oxides have potential application value in the field of supercapacitors and new energy materials. Traditional studies have shown that high specific surface area and porous structure are conducive to the supercapacitor electrodes exposing more electrochemically active sites and providing more abundant electrolyte ion transmission channels.
[0004] Among the many high entropy oxides, perovskite (ABO 3 ) structure has attracted much attention because such materials have excellent ionic and electronic mixed conductivity and excellent electrochemical activity, making them ideal material systems for supercapacitor electrodes. In the early experiments, the research team constructed a LaFeO 3 Oxide materials, but their specific surface area and specific capacitance values are not good. Summary of the invention
[0005] The present invention provides a porous high-entropy perovskite composite material and a preparation method and application thereof, which effectively solves the existing LaFeO 3 The technical problems of poor specific surface area and specific capacitance of oxide materials are solved, and a high-entropy perovskite composite material with excellent specific surface area and rich porous structure is provided.
[0006] The first object of the present invention is to provide a porous high entropy perovskite composite material, the chemical formula of which is La(Mn 0.2 Fe 0.2 Co 0.2Ni 0.2 Cu 0.2 ) 3 .
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned porous high entropy perovskite composite material, comprising the following steps:
[0008] Soluble La 3+ Salt, soluble Mn 2+ Salt, soluble Fe 3+ Salt, soluble Co 2+ Salt, soluble Ni 2+ Salt and soluble Cu 2+ The salt was dissolved in ethanol to obtain a first solution.
[0009] The first solution is mixed with an ethanol solution of an organic ligand to obtain a metal organic framework gel.
[0010] The metal organic framework gel is used as a porous template, the temperature is raised to 780-920° C., and sintered in an air atmosphere to obtain a high entropy perovskite composite material.
[0011] As a preferred embodiment, the La 3+ , Mn 2+ , Fe 3+ 、Co 2+ 、Ni 2+ and Cu 2+ The molar ratio is 5:1:1:1:1:1:1.
[0012] As a preferred embodiment, the La 3+ The molar ratio to the organic ligand is 0.9 to 1.1:1.
[0013] As a preferred embodiment, the organic ligand is 1,3,5-trimethylenedicarboxylic acid, 1,4-phthalic acid, 5-tert-butylphthalic acid, fumaric acid, 3,3,5,5-tetracarboxylic acid or 5-(pyridin-4-yl)isophthalic acid.
[0014] As a preferred implementation, the sintering time is 1.5 to 2.2 hours.
[0015] As a preferred embodiment, the preparation method of the metal organic framework gel is specifically as follows: the first solution is mixed with the ethanol solution of the organic ligand, stirred, and an initial gel is formed in 2 to 5 minutes, aged in air to obtain a wet gel, and then dried in multiple steps at 40°C, 50°C and 60°C for 8 hours respectively.
[0016] As a preferred embodiment, the soluble La 3+ The salt is La(NO3 ) 3 6H 2 O, LaCl 3 6H 2 O or La 2 (SO 4 ) 3 8H 2 O; Soluble Mn 2+ The salt is Mn(NO 3 ) 2 ·4H 2 O,MnCl 2 ·4H 2 O,MnSO 4 ·H 2 O or MnSO 4 ·4H 2 O; Soluble Fe 3+ The salt is Fe(NO 3 ) 3 9H 2 O, FeCl 3 6H 2 O or Fe 2 (SO 4 ) 3 ·H 2 O; soluble Co 2+ The salt is Co(NO 3 ) 2 6H 2 O,CoCl 2 ·H 2 O,CoCl 2 6H 2 O or CoSO 4 7H 2 O; Soluble Ni 2+ The salt is Ni(NO 3 ) 2 6H 2 O, NiCl 2 ·2H 2 O, NiCl 2 ·4H 2 O, NiCl 2 6H 2 O, NiSO 4 6H 2 O or NiSO 4 7H 2 O; Soluble Cu 2+ The salt is Cu(NO 3 ) 2 ·3H 2 O,CuCl 2 ·2H2 O or CuSO 4 ·5H 2 O.
[0017] As a preferred implementation, the heating rate is 3-8°C / min.
[0018] The third object of the present invention is to provide an application of the above-mentioned porous high entropy perovskite composite material in the preparation of supercapacitor electrode materials.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention is based on the oxide LaFeO 3 Based on Mn 2+ 、Co 2+ 、Ni 2+ and Cu 2+ Doping to replace part of Fe 3+ , thus obtaining the chemical formula La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3 The porous high-entropy perovskite composite material increases the specific surface area and porous structure of the high-entropy perovskite composite material, exposes more electrochemically active sites, and provides richer electrolyte ion transport channels, thereby improving the various performances of electrode materials prepared with the porous high-entropy perovskite composite material as raw material.
[0021] The present invention uses metal organic framework gel as a template to prepare a high entropy perovskite oxide material through a sintering process, which has an excellent specific surface area and a rich porous structure. The metal organic framework of the present invention is a porous organic-inorganic hybrid material formed by bridging metal ions / clusters with organic ligands, which has a rich pore structure and a high specific surface area. During the sintering process of converting to metal oxides, the porous structure is effectively continued to the derivative, thereby obtaining a high entropy perovskite composite material with a high specific surface area and a porous structure.
[0022] In addition, due to the coordination interference between various metal ions and the organic ligand 1,3,5-trimethylbenzene, the present invention can quickly form a metal organic framework (MOF) gel precursor under normal temperature and pressure conditions. Before the MOF gel template is formed, various metal ions can be fully mixed in the liquid phase and fixed in situ during the subsequent gelation process, and finally achieve molecular-level dispersion. Various metal sources obtain excellent uniformity in the precursor template, thereby reducing the generation of impurity phases in the subsequent sintering process, and obtaining a pure phase of high-entropy perovskite oxide.
[0023] The porous high-entropy perovskite composite material of the present invention has a simple preparation process and does not require additional conditions such as special complexing agents, pH regulators, heating, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a process flow chart of the preparation of the porous high entropy perovskite composite material of the present invention.
[0025] Figure 2 This is the XRD spectrum of the metal organic framework gel prepared in Example 1 of the present invention.
[0026] Figure 3 This is the XRD spectrum of the porous high entropy perovskite composite material prepared in Example 1 of the present invention.
[0027] Figure 4 XRD spectra of porous high entropy perovskite composite materials prepared at different sintering temperatures in Example 1 of the present invention and Comparative Examples 2 to 4.
[0028] Figure 5 This is a surface scanning energy spectrum diagram of the porous high entropy perovskite composite material prepared in Example 1 of the present invention, wherein a) is a SEM image of the energy spectrum scanning surface, b) is a superposition of all elements, and c) to i) correspond to the surface analysis energy spectra of O, Ni, Fe, Co, Cu, La, and Mn respectively.
[0029] Figure 6 These are SEM images of the porous high-entropy perovskite composite material prepared in Example 1 of the present invention, wherein a) is the SEM image at 500 nm, and b) is the SEM image at 300 nm.
[0030] Figure 7 TEM images of the porous high entropy perovskite composite material prepared in Example 1 of the present invention, wherein a) is the TEM image at 100 nm, b) is the TEM image at 300 nm, c) is the TEM image at 5 nm, and d) is the selected area diffraction pattern.
[0031] Figure 8 This is a nitrogen adsorption-desorption test curve of the porous high entropy perovskite composite material prepared in Example 1 of the present invention.
[0032] Fig. 9 This is a pore size distribution diagram of the porous high entropy perovskite composite material prepared in Example 1 of the present invention.
[0033] Fig.10 1 is a cyclic voltammetry (CV) curve of the porous high entropy perovskite composite material prepared in Example 1 of the present invention at different scanning rates.
[0034] Fig.11This is a constant current charge and discharge (GCD) curve of the porous high entropy perovskite composite material prepared in Example 1 of the present invention at different current densities.
[0035] Fig.12 This is a graph of the specific capacitance values of the porous high entropy perovskite composite material prepared in Example 1 of the present invention at different current densities.
[0036] Fig.13 This is a cyclic stability test curve of the porous high entropy perovskite composite material prepared in Example 1 of the present invention.
[0037] Fig.14 This is the AC impedance spectrum of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0039] The background technology of the present invention mentioned: the existing LaFeO 3 The specific surface area of the oxide material is not good, and the pore structure is not rich enough, which affects the performance of the high entropy oxide material as a supercapacitor electrode material. Based on the above technical problems, the present invention provides a porous high entropy perovskite composite material and its preparation method and application.
[0040] The technical solution of the present invention is analyzed and explained in detail below.
[0041] The present invention first provides a porous high entropy perovskite composite material, the chemical formula of which is La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3 .
[0042] In the above-mentioned perovskite composite material, the oxide LaFeO 3 Based on Mn 2+ 、Co 2+ 、Ni 2+ and Cu 2+ Doping to replace part of Fe 3+ , thus obtaining the chemical formula La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu0.2 ) 3 The porous high-entropy perovskite composite material increases the specific surface area and porous structure of the high-entropy perovskite composite material, exposes more electrochemically active sites, and provides richer electrolyte ion transport channels, thereby improving the electrochemical performance of the porous high-entropy perovskite composite material as an electrode material.
[0043] The method for preparing the porous high entropy perovskite composite material comprises the following steps:
[0044] Soluble La 3+ Salt, soluble Mn 2+ Salt, soluble Fe 3+ Salt, soluble Co 2+ Salt, soluble Ni 2+ Salt and soluble Cu 2+ The salt was dissolved in ethanol to obtain a first solution.
[0045] The first solution is mixed with an ethanol solution of an organic ligand to obtain a metal organic framework gel.
[0046] The metal organic framework gel is used as a porous template, the temperature is raised to 780-920° C., and sintered in an air atmosphere for 1.5-2.2 hours to obtain a porous high entropy perovskite composite material.
[0047] In order to obtain high-entropy perovskite La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3 The nanomaterial, the calcination time is 1.5 to 2.2 hours. Appropriate calcination conditions can optimize the crystal structure. In the temperature range of 780 to 820°C, especially the optimal 800°C, La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3The crystal structure can be effectively optimized to form a more stable and favorable phase, thereby improving its physical and chemical properties. Promote chemical reactions. Appropriate calcination temperature can promote chemical reactions between raw materials, so that Mn, Fe, Co, Ni and Cu can be more fully doped into the structure of the target product, thereby improving the purity and yield of the product. Avoid the generation of impurities. Under appropriate calcination conditions, the generation of impurities can be avoided or reduced to ensure the quality of the product. Save energy. Selecting the optimal calcination temperature can maximize energy conservation and reduce production costs while ensuring product quality. If the calcination conditions of the present invention are not adopted, the composite material will have poor performance due to insufficient or excessive calcination. Insufficient calcination will result in an incomplete crystal structure, and a too low calcination temperature will result in the inability to fully form a crystal structure, affecting the physical and chemical properties of the product. Insufficient chemical reactions, the chemical reactions between the raw materials cannot be fully carried out, resulting in low product purity and poor yield. The impurity content is high, and low-temperature calcination cannot effectively remove impurities in the raw materials, affecting the quality of the product. Excessive calcination will lead to a decrease in the specific surface area of the product. Under high temperature conditions, the pore structure of the sintered solid solution is reduced, which is not conducive to the transmission of electrolyte ions, resulting in a decrease in the supercapacitor performance of the material. In addition, energy consumption increases, and excessively high calcination temperatures will increase energy consumption and increase production costs.
[0048] In order to obtain a porous high-entropy perovskite composite material with higher yield and better purity, the La 3+ , Mn 2+ , Fe 3+ 、Co 2 + 、Ni 2+ and Cu 2+ The molar ratio is 5:1:1:1:1:1:1.
[0049] It should be emphasized that the La 3+ The molar ratio of the organic ligand to the organic ligand is 0.9 to 1.1:1. If the ratio is too low, gel cannot be formed, which is not conducive to the uniformity of the sintered product. In addition, a low ratio will lead to a long gel formation time, reduce the material preparation efficiency, and increase production costs; a high ratio will lead to a too fast formation rate of metal organic framework (MOFs) gel, which will lead to unevenness inside the MOFs gel precursor, and the dispersion of the sintered material particles may also be affected, thereby reducing the supercapacitor performance. On the other hand, the content of the effective secondary unit inside the MOFs gel precursor is low, and the pore structure of the high entropy perovskite material obtained by sintering is reduced, and the specific surface area is reduced, which is not conducive to the improvement of supercapacitor performance.
[0050] It should be noted that the organic ligand is 1,3,5-trimethylenedicarboxylic acid, 1,4-phthalic acid, 5-tert-butylphthalic acid, fumaric acid, 3,3,5,5-tetracarboxylic acid or 5-(pyridin-4-yl)isophthalic acid.
[0051] In order to obtain a metal organic framework gel with better performance, the preparation method of the metal organic framework gel is specifically as follows: the first solution is mixed with an ethanol solution of an organic ligand, stirred, and an initial gel is formed in 2 to 5 minutes, aged in air to obtain a wet gel, and dried in multiple steps at 40°C, 50°C and 60°C for 8 hours respectively.
[0052] It should be noted that the soluble La 3+ The salt is La(NO 3 ) 3 6H 2 O, LaCl 3 6H 2 O or La 2 (SO 4 ) 3 8H 2 O; Soluble Mn 2+ The salt is Mn(NO 3 ) 2 ·4H 2 O,MnCl 2 ·4H 2 O,MnSO 4 ·H 2 O or MnSO 4 ·4H 2 O; Soluble Fe 3+ The salt is Fe(NO 3 ) 3 9H 2 O, FeCl 3 6H 2 O or Fe 2 (SO 4 ) 3 ·H 2 O; soluble Co 2+ The salt is Co(NO 3 ) 2 6H 2 O,CoCl 2 ·H 2 O,CoCl 2 6H 2 O or CoSO 4 7H 2 O; Soluble Ni 2+ The salt is Ni(NO 3 ) 2 6H2 O, NiCl 2 ·2H 2 O, NiCl 2 ·4H 2 O, NiCl 2 6H 2 O, NiSO 4 6H 2 O or NiSO 4 7H 2 O; Soluble Cu 2+ The salt is Cu(NO 3 ) 2 ·3H 2 O,CuCl 2 ·2H 2 O or CuSO 4 ·5H 2 O.
[0053] In order to further improve the electrochemical performance of the porous high-entropy perovskite composite material, the heating rate is 3 to 8 ° C / min. In some high-entropy electrode materials, the heating rate will affect its pore structure, grain size, uniformity and crystallinity, thereby affecting its electrochemical performance. First, it affects the specific surface area: Generally speaking, when the heating rate is low, more holes may be formed on the surface of the material, thereby increasing the specific surface area. The increase in specific surface area helps to improve the mobility and transmission capacity of electrolyte ions in the energy storage process of the electrode material, thereby improving its supercapacitor performance. However, too high a heating rate may cause the surface of the material to be too dense, reduce the specific surface area, and be detrimental to the improvement of supercapacitor performance. Second, it affects the pore size distribution and dispersion: at a low heating rate, the pore size distribution of the electrode material is narrow and the pore size is more uniform, which is conducive to the diffusion and transmission of electrolyte ions during charging and discharging. At the same time, a low heating rate also helps to improve the dispersion of the material, making the material particles more evenly distributed, thereby improving the supercapacitor performance. On the contrary, at a high heating rate, the pore size distribution of the material may become wider and uneven, and the dispersion of the material particles may also be affected, thereby reducing the supercapacitor performance. Third, it affects the grain size of the material: a heating rate that is too low will increase the time for grain growth and form larger grains. Larger grains will reduce the mechanical properties of the material and lead to a decrease in cycle stability during charging and discharging. A heating rate that is too high will lead to incomplete sintering reaction and the formation of an amorphous phase. The crystallization performance of the material is poor and it is easy to contain impurities, which may change the energy storage mechanism of the material, thereby affecting the size of the material's specific capacitance.
[0054] The technical effects of the present invention are described in detail below through specific embodiments and comparative examples.
[0055] Example 1
[0056] A method for preparing a porous high entropy perovskite composite material, such as Figure 1 As shown, the following steps are included:
[0057] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2 O, 2.0mmol Co(NO 3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0058] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes, and aging in air for 12 hours to obtain a wet MOF gel, and drying the wet MOF gel in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0059] S3, using the metal organic framework gel as a porous template, heating to 800° C. at a rate of 5° C. / min, sintering for 2 hours in an air atmosphere, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0060] Example 2
[0061] A method for preparing a porous high entropy perovskite composite material comprises the following steps:
[0062] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2O, 2.0mmol Co(NO 3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0063] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes, and aging in air for 12 hours to obtain a wet MOF gel, and drying the wet MOF gel in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0064] S3, using the metal organic framework gel as a porous template, heating to 920° C. at a rate of 5° C. / min, sintering for 2 h in an air atmosphere, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0065] Example 3
[0066] A method for preparing a porous high entropy perovskite composite material comprises the following steps:
[0067] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2 O, 2.0mmol Co(NO 3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0068] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes, and aging in air for 12 hours to obtain a wet MOF gel, and drying the wet MOF gel in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0069] S3, using the metal organic framework gel as a porous template, heating to 780° C. at a rate of 5° C. / min, sintering in an air atmosphere for 2 h, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0070] Example 4
[0071] A method for preparing a porous high entropy perovskite composite material comprises the following steps:
[0072] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2 O, 2.0mmol Co(NO 3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0073] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes, and aging in air for 12 hours to obtain a wet MOF gel, and drying the wet MOF gel in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0074] S3, using the metal organic framework gel as a porous template, heating to 850° C. at a rate of 5° C. / min, sintering for 2 h in an air atmosphere, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0075] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:
[0076] Comparative Example 1
[0077] Compared with Example 1, the difference is that Mn is not used. 2+ 、Co 2+ 、Ni 2+ and Cu 2+ Doping to replace part of Fe 3+ , only the chemical formula LaFeO 3 of oxides.
[0078] An oxide LaFeO 3 The preparation method comprises the following steps:
[0079] S1, 10mmol La(NO 3 ) 3 6H 2 O and 10mmol Fe(NO 3 ) 3 9H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0080] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes, and aging in air for 12 hours to obtain a wet MOF gel, and drying the wet MOF gel in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0081] S3, using the metal organic framework gel as a porous template, heating to 500-800°C at a rate of 5°C / min, sintering in an air atmosphere for 2h, and naturally cooling to room temperature to obtain a high oxide LaFeO 3 .
[0082] Comparative Example 2
[0083] Compared with Example 1, the difference is that 800°C is reduced to 500°C.
[0084] A method for preparing a porous high entropy perovskite composite material comprises the following steps:
[0085] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2 O, 2.0mmol Co(NO 3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0086] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes. After aging in air for 12 hours, a wet MOF gel is obtained. The wet MOF gel is dried in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0087] S3, using the metal organic framework gel as a porous template, heating to 500° C. at a rate of 5° C. / min, sintering for 2 h in an air atmosphere, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0088] Comparative Example 3
[0089] Compared with Example 1, the difference is that 800°C is reduced to 600°C.
[0090] A method for preparing a porous high entropy perovskite composite material comprises the following steps:
[0091] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2 O, 2.0mmol Co(NO3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0092] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes. After aging in air for 12 hours, a wet MOF gel is obtained. The wet MOF gel is dried in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0093] S3, using the metal organic framework gel as a porous template, heating to 600° C. at a rate of 5° C. / min, sintering for 2 h in an air atmosphere, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0094] Comparative Example 4
[0095] Compared with Example 1, the difference is that 800°C is reduced to 700°C.
[0096] A method for preparing a porous high entropy perovskite composite material comprises the following steps:
[0097] S1, 10mmol La(NO 3 ) 3 6H 2 O, 2.0mmol Mn(NO 3 ) 2 ·4H 2 O, 2.0mmol Fe(NO 3 ) 3 9H 2 O, 2.0mmol Co(NO 3 ) 2 6H 2 O, 2.0mmolNi(NO 3 ) 2 6H 2 O and 2.0 mmol Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of ethanol solution to form a transparent first solution.
[0098] S2, dissolving 10 mmol of 1,3,5-trimethylbenzenecarboxylic acid in 30 mL of ethanol to form a transparent second solution; quickly mixing the first solution and the second solution, and then vigorously stirring to form a metal organic framework (MOF) gel within 2 to 5 minutes. After aging in air for 12 hours, a wet MOF gel is obtained. The wet MOF gel is dried in an oven at 40°C, 50°C and 60°C for 8 hours respectively to obtain a metal organic framework gel.
[0099] S3, using the metal organic framework gel as a porous template, heating to 700° C. at a rate of 5° C. / min, sintering for 2 hours in an air atmosphere, and naturally cooling to room temperature to obtain a high entropy perovskite composite material.
[0100] For the porous high entropy perovskite composite material prepared in the embodiment of the present invention, the oxide LaFeO prepared in Comparative Example 1 3 The performance test results of the high entropy perovskite composite materials prepared in Comparative Examples 2 to 4 are as follows.
[0101] The porous high entropy perovskite composite material prepared in Example 1 of the present invention and the oxide LaFeO prepared in the comparative example 3 The specific surface area and the maximum specific capacitance at a current density of 1 A / g are shown in Table 1, and the comparison of specific capacitance values at different current densities is shown in Table 2.
[0102] Table 1 Comparison of material properties of Example 1 of the present invention and Comparative Example 1
[0103] Maximum specific capacitance (at 1A / g current density) Specific surface area Comparative Example 1 241.3F / g <![CDATA[41m 2 / g]]> Example 1 609.3F / g <![CDATA[43.2m 2 / g]]>
[0104] Table 2 Comparison of specific capacitance values of materials in Example 1 of the present invention and Comparative Example 1 at different current densities
[0105] 1A / g 2A / g 3A / g 5A / g 10A / g 20A / g Comparative Example 1 241.3F / g 203.8F / g 186.6F / g 177F / g 174F / g 164F / g Example 1 609.3F / g 567.7F / g 533.9F / g 477.5F / g 438.8F / g 382.0F / g
[0106] It can be seen from Table 1 and Table 2 that compared with the oxide LaFeO prepared in Comparative Example 1 3 In comparison, the porous high entropy perovskite composite material prepared by the present invention has a larger specific surface area and pore structure, and has a better specific capacitance value as an electrode material.
[0107] Figure 2 This is the XRD spectrum of the metal organic framework gel prepared in Example 1 of the present invention. Different substances have specific atomic species, atomic arrangement and lattice parameters. Under the action of X-rays, different crystal faces of the crystals undergo their own diffraction, presenting specific diffraction patterns. X-ray powder diffraction (XRD) is used to determine the structure of the powder. Figure 2Well-arranged diffraction peaks can be observed, and the peaks at 6.2°, 10.2°, 10.9°, 12.3°, 17.9°, 20.1° and 27.6° are consistent with the simulated standard diffraction pattern of MIL-100(Fe) (CCDC No. 640536). The presence of broad peaks is because the metal-organic framework exists in the form of gel with low crystallinity.
[0108] Figure 3 This is the XRD spectrum of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. Figure 3 It can be seen that strong diffraction peaks are shown at 22.90°, 32.57°, 32.65°, 40.32°, 46.79°, 58.31°, 68.41° and 77.83°, corresponding to the reflections of the (012), (110), (104), (006), (024), (018), (208) and (128) crystal planes, respectively, belonging to the perovskite crystal structure of the R-3c space group, which is consistent with the diffraction peaks of the perovskite material (JCPDS No.82-1963) in the standard PDF card in the range of 20° to 80°, and no other impurities appear, indicating that the present invention prepares a pure phase powder with a perovskite structure.
[0109] Figure 4 The XRD spectra of the porous high entropy perovskite composite materials prepared at different sintering temperatures in Example 1 and Comparative Examples 2 to 4 of the present invention are shown in FIG. Figure 4 It can be seen that the purity of the sample increases with the increase of sintering temperature, and a pure phase high entropy structure can be obtained at a sintering temperature of 800°C. At a sintering temperature below 800°C, impurity phases exist in the sample.
[0110] Figure 5 This is a surface scanning energy spectrum of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. Figure 5 It can be seen that the sample contains O, Ni, Fe, Co, Cu, La, Mn and other elements, and the various elements are evenly distributed in the sample. Combined with the perovskite structure confirmed by the XRD spectrum, it shows that the prepared sample is a high-entropy perovskite oxide La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3 .
[0111] Figure 6 The SEM images of the porous high entropy perovskite composite material prepared in Example 1 of the present invention, wherein a) is the SEM image at 500nm, and b) is the SEM image at 300nm. Figure 6It can be seen that the prepared porous high-entropy perovskite composite material is composed of interconnected nanoparticles with a diameter of 10 to 100 nm, which are elliptical in shape and have good dispersion.
[0112] Figure 7 TEM images of the porous high entropy perovskite composite material prepared in Example 1 of the present invention, wherein a) is a TEM image at 100nm, b) is a TEM image at 300nm, c) is a TEM image at 5nm, and d) is a selected area diffraction pattern. Figure 7 It can be clearly seen from Figures a) and b) that the particles have clear boundaries, uniform sizes, and interconnected structures, which is consistent with Figure 6 The SEM results are consistent with those in . Figure 7 The lattice distance of ~0.388nm measured in Figure c) is consistent with the standard plane spacing of the (012) diffraction crystal plane in the perovskite structure. In addition, Figure 7 Figure d) also shows that the nanoparticles are single crystal phases of high entropy perovskite, and three diffraction crystal planes (012), (006) and (0-14) can be marked, with corresponding lattice spacings of 0.388, 0.223 and 0.317 nm, respectively. This is consistent with the XRD characterization results, and the lattice fringes are clear and sharp, indicating that the sample has a high purity.
[0113] Figure 8 This is a nitrogen adsorption-desorption test curve of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. Figure 8 It can be seen that the specific surface area of the sample is 43.2m 2 / g, which is higher than the high entropy perovskite oxide in Comparative Example 1.
[0114] Fig. 9 This is a pore size distribution diagram of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. Fig. 9 It can be seen that the pore size of the sample is mainly concentrated in the range of 2nm to 10nm, which is a typical mesoporous structure, which is conducive to the rapid movement of electrolyte ions during energy storage.
[0115] Electrode preparation and test conditions:
[0116] Take 80% (by weight) of high entropy perovskite oxide material, 10% (by weight) of conductive carbon black and 10% (by weight) of polytetrafluoroethylene binder, mix them evenly, make them into slurry, and then brush them on a 1cm×2cm nickel foam current collector; the obtained electrode is vacuum dried at 60℃ for 24 hours. The electrochemical test uses 3M KOH as the electrolyte, 1cm 2The platinum sheet was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and a three-electrode test system was constructed, and the CHI660E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) was used for recording. The characterization included cyclic voltammetry (CV), constant current charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS). The EIS data were tested in the range of 0.1Hz to 100kHz with an amplitude of 10mV.
[0117] Fig.10 The cyclic voltammetry (CV) curves of the porous high entropy perovskite composite material prepared in Example 1 of the present invention at different scanning rates are shown in FIG. Fig.10 It can be seen that the CV curves of the samples in the potential range of 0-0.5 V all show obvious redox peaks related to the Faraday redox reaction. As the scan rate increases, all curves maintain similar shapes, indicating that the porous high-entropy perovskite composite material prepared in Example 1 has good pseudocapacitive characteristics and excellent rate amplification performance.
[0118] Fig.11 The following is a constant current charge and discharge (GCD) curve of the porous high entropy perovskite composite material prepared in Example 1 of the present invention at different current densities. Fig.11 It can be seen that the existence of a voltage platform can be observed in the constant current charge and discharge curves under different current densities, indicating the pseudocapacitive characteristics of the sample. This energy storage mechanism is conducive to obtaining a high specific capacitance. In addition, the sample has a charge and discharge time of up to 818 seconds at a current density of 1A / g, which proves the excellent electrochemical properties of the sample.
[0119] Fig.12 Graph showing the specific capacitance value of the present invention at different current densities. Fig.12 It can be seen that the specific capacitance of the porous high-entropy perovskite composite material prepared in Example 1 is as high as 609.3F / g, which is much higher than similar high-entropy oxide electrode materials. The specific capacitances of the samples at current densities of 1A / g, 2A / g, 3A / g, 5A / g, 10A / g, and 20A / g are 609.3F / g, 567.7F / g, 533.9F / g, 477.5F / g, 438.8F / g, and 382.0F / g, respectively. At a current density of 20A / g, the specific capacitance can be maintained at 62.7% of that at a current density of 1A / g, indicating that the sample has excellent rate amplification performance, which is attributed to the fact that the porous high-entropy perovskite composite material prepared by this method has a high specific surface area and rich pore structure, which is conducive to the rapid transport of electrolyte ions.
[0120] Fig.13 This is a test curve of the cyclic stability of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. Fig.13 It can be seen that after 3000 cycles of charge and discharge testing, the capacitance retention rate of the sample is as high as 91.4%.
[0121] Fig.14 This is the AC impedance spectrum of the porous high entropy perovskite composite material prepared in Example 1 of the present invention. Fig.14 From the fitting, it can be seen that the equivalent series resistance value of the sample is 0.848Ω, and the charge transfer resistance value is 2.6Ω, both of which are low, indicating that the prepared sample has low resistance and excellent charge transfer performance, which is beneficial to the improvement of supercapacitor performance.
[0122] In summary, the present invention is based on the oxide LaFeO 3 Based on Mn 2+ 、Co 2+ 、Ni 2+ and Cu 2+ Doping to replace part of Fe 3+ , thus obtaining the chemical formula La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3 The porous high-entropy perovskite composite material increases the specific surface area and porous structure of the high-entropy perovskite composite material, exposes more electrochemically active sites, and provides richer electrolyte ion transport channels, thereby improving the various performances of electrode materials prepared with the porous high-entropy perovskite composite material as raw material.
[0123] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A porous high entropy perovskite composite material, characterized in that: Its chemical formula is La(Mn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 )O3.
2. A method for preparing the porous high entropy perovskite composite material according to claim 1, characterized in that: The following steps are involved: Soluble La 3+ Salt, soluble Mn 2+ Salt, soluble Fe 3+ Salt, soluble Co 2+ Salt, soluble Ni 2+ Salt and soluble Cu 2 + The salt is dissolved in ethanol to obtain a first solution; Mixing the first solution with an ethanol solution of an organic ligand to obtain a metal organic framework gel; The metal organic framework gel is used as a porous template, the temperature is raised to 780-920° C., and sintered in an air atmosphere to obtain a high entropy perovskite composite material.
3. The preparation method according to claim 2, characterized in that: The La 3+ , Mn 2+ , Fe 3+ 、Co 2+ 、Ni 2+ and Cu 2+ The molar ratio is 5:1:1:1:1:1:
1.
4. The preparation method according to claim 3, characterized in that: The La 3+ The molar ratio to the organic ligand is 0.9 to 1.1:
1.
5. The preparation method according to claim 4, characterized in that: The organic ligand is 1,3,5-trimethylenedicarboxylic acid, 1,4-phthalic acid, 5-tert-butylphthalic acid, fumaric acid, 3,3,5,5-tetracarboxylic acid or 5-(pyridin-4-yl)isophthalic acid.
6. The preparation method according to claim 2, characterized in that: The sintering time is 1.5 to 2.2 hours.
7. The preparation method according to claim 2, characterized in that: The preparation method of the metal organic framework gel is specifically as follows: the first solution is mixed with the ethanol solution of the organic ligand, stirred, and an initial gel is formed in 2 to 5 minutes, aged in air to obtain a wet gel, and dried in multiple steps, respectively at 40° C., 50° C. and 60° C. for 8 hours.
8. The preparation method according to claim 2, characterized in that: The soluble La 3+ The salt is La(NO3)3·6H2O, LaCl3·6H2O or La2(SO4)3·8H2O; soluble Mn 2+ The salt is Mn(NO3)2·4H2O, MnCl2·4H2O, MnSO4·H2O or MnSO4·4H2O; soluble Fe 3+ The salt is Fe(NO3)3·9H2O, FeCl3·6H2O or Fe2(SO4)3·H2O; soluble Co 2+ The salt is Co(NO3)2·6H2O, CoCl2·H2O, CoCl2·6H2O or CoSO4·7H2O; soluble Ni 2+ The salt is Ni(NO3)2·6H2O, NiCl2·2H2O, NiCl2·4H2O, NiCl2·6H2O, NiSO4·6H2O or NiSO4·7H2O; soluble Cu 2+ The salt is Cu(NO3)2·3H2O, CuCl2·2H2O or CuSO4·5H2O.
9. The preparation method according to claim 2, characterized in that: The heating rate is 3-8°C / min.
10. Use of the porous high entropy perovskite composite material according to claim 1 in preparing a supercapacitor electrode material.
Citation Information
Cited By
Perovskite type sodium-ion battery negative electrode material for in-situ precipitation of nano high-entropy alloy and preparation method of perovskite type sodium-ion battery negative electrode material
CN120413643A
High-entropy perovskite material and preparation method and application thereof
CN120649063A